A core-shell structure filler and its preparation method and application in polyetherimide-based energy storage composite dielectric film

By introducing core-shell structure filler prepared by magnetron sputtering into the polyetherimide matrix, the problems of poor energy storage characteristics and high dielectric loss of polyetherimide-based energy storage composite media in high temperature environments are solved, and the problem of poor energy storage characteristics and high dielectric loss in high temperature environments is achieved. It has excellent high-temperature energy storage characteristics and improved insulation performance, and is suitable for applications such as high-voltage flexible direct transmission and new energy vehicles.

CN117757147BActive Publication Date: 2024-12-13HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311726912.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2024-12-13
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

The existing polyetherimide-based energy storage composite media have poor energy storage characteristics and high dielectric loss in high temperature environments, making it difficult to meet the needs of long-term service environments in applications such as high-voltage flexible direct transmission and new energy vehicles.

Method used

Core-shell structure filler is used to coat the boron nitride shell layer on the surface of magnesium oxide particles through magnetron sputtering technology to form BN@MgO particles and introduce them into the polyetherimide matrix to form a heterostructure to inhibit shock Pass through paths and carrier transport to improve insulation performance.

Benefits of technology

It significantly improves the insulation performance and energy storage density of composite media over a wide temperature range, the discharge energy density reaches 3.9J/cm3, the breakdown strength is improved, and the leakage current density is reduced, making it suitable for applications in high temperature and high field environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117757147B_ABST
    Figure CN117757147B_ABST
Patent Text Reader

Abstract

A core-shell structure filler, a preparation method thereof, and an application in a polyetherimide-based energy storage composite dielectric film. The present invention belongs to the field of energy storage dielectric materials and their preparation. The purpose of the present invention is to solve the technical problems of poor high-temperature energy storage characteristics and high dielectric loss of existing polyetherimide-based energy storage composite dielectrics. The present invention uses magnetron sputtering technology to prepare core-shell structure fillers, and obtains BN@MgO particles with a large energy band gap difference by regulating the sputtering time of magnetron sputtering. Boron nitride-coated magnesium oxide particles are then introduced into the polyetherimide matrix, and a heterogeneous structure is formed inside the boron nitride-coated magnesium oxide particles to build a local electric field to suppress the breakdown path. This core-shell structure can effectively offset the effect of an external electric field, and can effectively suppress the transport of carriers inside the composite medium, reducing the current density of the composite medium, and ultimately effectively improving the insulation performance of the composite medium over a wide temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy storage dielectric materials and preparation thereof, and specifically relates to a core-shell structure filler and a preparation method thereof and application thereof in a polyetherimide-based energy storage composite dielectric film. Background Art

[0002] Dielectric capacitors have the characteristics of high power density and fast charge and discharge rate, and are in great demand in industries such as high-voltage flexible direct current transmission and new energy vehicles. However, there are many bottlenecks in the research of energy storage characteristics and temperature stability of dielectric materials for capacitors, especially in high-temperature and high-field harsh service environments such as high-voltage flexible direct current transmission converter valves and new energy vehicle and electric vehicle inverters.

[0003] Polyetherimide (PEI) has good thermal stability and is often used as a high-temperature energy storage dielectric, but its low dielectric constant limits its further application. Polymer nanocomposite dielectrics combine the excellent dielectric properties of inorganic fillers with the high breakdown field strength and easy processing of the polymer matrix and are widely used in film capacitors. However, due to the large difference in dielectric properties between nanofillers and polymer matrices, the breakdown strength of nanocomposite dielectrics is reduced. Therefore, how to synergistically improve energy storage performance and effectively avoid charge accumulation is a challenge faced by the energy storage dielectric industry. It is urgent to develop dielectric materials with high energy storage characteristics suitable for long-term use environments. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems of poor high temperature energy storage characteristics and high dielectric loss of existing polyetherimide-based energy storage composite media, and to provide a core-shell structure filler and a preparation method thereof and application in polyetherimide-based energy storage composite dielectric films.

[0005] The technical solution of the present invention is achieved by the following methods:

[0006] One of the purposes of the present invention is to provide a core-shell structure filler, wherein the core of the filler is magnesium oxide particles and the shell is boron nitride.

[0007] It is further defined that the particle size of the magnesium oxide particles is 250-300 nm and the shell thickness is 40-100 nm.

[0008] The second object of the present invention is to provide a method for preparing a core-shell structure filler, wherein:

[0009] Boron nitride is used as a target material and magnesium oxide particles are used as a matrix. The target material is bombarded by magnetron sputtering to coat a boron nitride shell layer on the surface of the magnesium oxide particles.

[0010] It is further defined that the magnetron sputtering process has a power of 50-70 W, a time of 1.5-3 h, and a target-substrate distance of 15-18 cm.

[0011] It is further defined that the magnetron sputtering time is 2-2.5 hours.

[0012] The third object of the present invention is to provide an application of the core-shell structure filler prepared by the above method in polymer-based energy storage dielectric materials.

[0013] A fourth object of the present invention is to provide a polyetherimide-based energy storage composite dielectric film having excellent high-temperature energy storage properties, wherein the polyetherimide-based energy storage composite dielectric film comprises the above-mentioned core-shell structure filler.

[0014] It is further defined that the mass ratio of the core-shell structure filler to the polyetherimide in the film is (0.01-0.02):1.

[0015] It is further defined that the film thickness is 10-12 μm.

[0016] A fifth object of the present invention is to provide a method for preparing a polyetherimide-based energy storage composite dielectric film having excellent high-temperature energy storage properties, wherein:

[0017] S1: dissolving polyetherimide in N-methylpyrrolidone, then adding the core-shell structure filler, mixing well, and removing bubbles to obtain a slurry;

[0018] S2: The obtained slurry is made into a wet film by doctor blade coating, and then dried by gradient heating to obtain a polyetherimide-based energy storage composite dielectric film.

[0019] It is further defined that the slurry concentration in S1 is 0.1-0.15 g / mL.

[0020] It is further defined that in S1, degassing is performed by vacuuming.

[0021] It is further defined that the gradient temperature rising program in S2 is: 60-80°C for 3-5h, 110-130°C for 1-3h, 140-160°C for 1-3h, 180-220°C for 1-3h, and finally at 180-220°C under vacuum for 3-5h.

[0022] A sixth object of the present invention is to provide a polyetherimide-based energy storage composite dielectric film with excellent high-temperature energy storage properties for use in capacitors.

[0023] Compared with the prior art, the present invention has the following significant effects:

[0024] The present invention uses magnetron sputtering technology to prepare core-shell structure fillers, bombards boron nitride targets, allows boron nitride to fall naturally and coat magnesium oxide, and obtains BN@MgO particles with a large energy band gap difference by adjusting the sputtering time of magnetron sputtering. Then, the boron nitride coated magnesium oxide particles are introduced into the polyetherimide matrix, and a heterogeneous structure is formed inside the boron nitride coated magnesium oxide particles to build a local electric field to suppress the breakdown path. In this core-shell structure, an electric field in the opposite direction to the external electric field is always present at the heterojunction interface due to electron transfer, which can effectively offset the effect of the external electric field and effectively inhibit the transport of carriers inside the composite medium, reducing the current density of the composite medium, and finally effectively improving the insulation performance of the composite medium in a wide temperature range. The results show that the prepared composite medium has a discharge energy density of 3.9 J / cm at 150°C, 460 kV / mm, and a charge and discharge efficiency of 90%. 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a transmission electron microscope image of the BN@MgO particles prepared in Example 3;

[0026] Figure 2 SEM and EDS images of the BN@MgO particles prepared in Example 3;

[0027] Figure 3 XRD comparison spectra of composite media obtained in different embodiments, magnesium oxide-doped polyetherimide film, magnesium oxide and boron nitride;

[0028] Figure 4 The curves showing the change of dielectric constant and dielectric loss with frequency of the composite medium and magnesium oxide-doped polyetherimide film obtained in different embodiments at 150°C;

[0029] Figure 5 Weibull distribution diagram of breakdown field strength of composite dielectrics and magnesium oxide-doped polyetherimide films obtained in different embodiments at 150°C;

[0030] Figure 6 A comparison diagram of energy storage characteristics of composite media and magnesium oxide-doped polyetherimide films obtained in different embodiments at 150°C;

[0031] Figure 7 Leakage current density diagram of the composite dielectric and magnesium oxide-doped polyetherimide film obtained in different embodiments at 150°C. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0034] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0035] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0037] Example 1: The preparation method of the polyetherimide-based energy storage composite dielectric film with excellent high-temperature energy storage characteristics in this example is carried out according to the following steps:

[0038] (1) Preparation of core-shell structured BN@MgO particles:

[0039] Boron nitride is used as the target material and magnesium oxide particles (with an average particle size of 250 nm) are used as the substrate. The target is bombarded with a boron nitride shell on the surface of the magnesium oxide particles by magnetron sputtering. The atmosphere is a mixture of 75% argon and 25% nitrogen, the sputtering pressure is 1.3 Pa, the sputtering temperature is room temperature, the sputtering power is 60 W, the sputtering time is 1.5 h, and the target-substrate distance is 15 cm. A boron nitride shell with a thickness of 40 nm is obtained, which is recorded as BN@MgO.

[0040] (2) Preparation of composite dielectric films:

[0041] First, polyetherimide was dissolved in N-methylpyrrolidone, and then BN@MgO particles were added. The mass ratio of polyetherimide particles to BN@MgO particles was 1:0.015. The mixture was stirred at 60°C and 300 rpm until uniformly mixed. Then, the mixture was allowed to stand in a vacuum environment at 30°C for 20 min to remove bubbles, and a slurry with a concentration of 0.13 g / mL was obtained.

[0042] Then, the above slurry was horizontally scraped at a speed of 5 cm / s to form a wet film, and then dried by gradient heating. The gradient heating program was: drying at 70°C for 4 hours, drying at 120°C for 2 hours, drying at 150°C for 2 hours, and drying at 200°C for 2 hours. Finally, it was dried in a vacuum environment at 200°C for 4 hours to obtain a polyetherimide-based energy storage composite dielectric film with a BN@MgO particle doping amount of 1.5wt.% and a thickness of 12μm, referred to as PEI / BN@MgO-1.5 (1.5h).

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that in step (1), the magnetron sputtering time of BN@MgO particles is 2 hours, the shell thickness is 60 nm, and the remaining operation process and parameter settings are the same as those in embodiment 1. A polyetherimide-based energy storage composite dielectric film is obtained, referred to as PEI / BN@MgO-1.5 (2h).

[0045] Example 3

[0046] The difference between this embodiment and embodiment 1 is that in step (1), the magnetron sputtering time of BN@MgO particles is 2.5 hours, the shell thickness is 80 nm, and the remaining operation process and parameter settings are the same as those in embodiment 1. A polyetherimide-based energy storage composite dielectric film is obtained, referred to as PEI / BN@MgO-1.5 (2.5h).

[0047] Example 4

[0048] The difference between this embodiment and embodiment 1 is that in step (1), the magnetron sputtering time of BN@MgO particles is 3 hours, the shell thickness is 100 nm, and the remaining operation process and parameter settings are the same as those in embodiment 1. A polyetherimide-based energy storage composite dielectric film is obtained, referred to as PEI / BN@MgO-1.5 (3h).

[0049] Comparative Example 1

[0050] The difference between this comparative example and Example 1 is that step (1) is omitted, BN@MgO particles in step (2) are replaced by MgO particles, the doping amount remains unchanged, and the remaining operation process and parameter settings are the same as those of Example 1. A polyetherimide-based energy storage composite dielectric film is obtained, referred to as PEI / MgO-1.5.

[0051] Effect example

[0052] The microstructure of the BN@MgO particles prepared in Example 3 was characterized, and the TEM image is as follows: Figure 1 As shown, SEM and EDS images are Figure 2 As shown, from the TEM image, it can be seen that the magnesium oxide particle size is 250nm and the shell thickness is 80nm.

[0053] The structure and performance of the composite media obtained in Examples 1-4 and Comparative Example 1 were characterized, and the results are as follows:

[0054] Figure 3 The XRD comparison patterns of the five composite media and MgO and BN fillers prepared in Examples 1-4 and Comparative Example 1 are shown in FIG. Figure 3 It can be seen that the characteristic diffraction peak (002) of BN appears in the composite medium, indicating that BN is successfully introduced into the filler.

[0055] Figure 4 The curves of dielectric constant and dielectric loss of five composite dielectrics prepared in Examples 1-4 and Comparative Example 1 at 150°C as a function of frequency are shown in FIG. Figure 4 It can be seen that the dielectric constant of all composite media shows almost frequency-independent characteristics within the studied frequency range (10-106Hz), and has good frequency stability. The longer the sputtering time, the greater the dielectric constant of the composite medium. In addition, the interfacial polarization of the accumulated charge on the interface between the filling phase and PEI provides a larger dipole moment, which also helps to increase the dielectric constant.

[0056] Figure 5 is the Weibull distribution diagram of the breakdown field strength of the five composite media prepared in Examples 1-4 and Comparative Example 1 at 150°C. Figure 5 It can be seen that the breakdown strength of the composite medium prepared in Example 3 can reach 485.0 kV / mm, which indicates that due to the different affinities of the materials to electrons, a heterogeneous structure is formed inside the particles to build a local electric field to suppress the breakdown path, thereby improving the breakdown field strength of the composite medium.

[0057] Figure 6 is a comparison chart of the energy storage characteristics of the five composite media prepared in Examples 1-4 and Comparative Example 1 at 150°C. Figure 6 It can be seen that when the energy storage efficiency of the composite medium prepared in Example 3 is 90%, the discharge energy density reaches 3.9 J / cm 3 This is mainly due to the fact that the high breakdown field strength and the reduction of conductivity loss enhance the energy storage density, thereby greatly improving the energy storage efficiency.

[0058] Figure 7 is a leakage current density diagram of five composite media prepared in Examples 1-4 and Comparative Example 1, Figure 7 It can be seen that the composite medium prepared in Example 3 achieves a minimum leakage current density of 6.87×10 - 8 A. Since in this core-shell structure, an electric field in the opposite direction to the external electric field is always formed at the heterojunction interface due to electron transfer, the effect of the external electric field can be effectively offset, and the transport of carriers inside the composite medium can be effectively inhibited, thereby reducing the leakage current density of the composite medium. The leakage current density of Examples 1-4 is significantly reduced compared with that of Comparative Example 1.

[0059] In summary, the core-shell structured inorganically doped polyetherimide energy storage composite medium prepared in the present invention has good dielectric properties and high breakdown strength.

[0060] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a polyetherimide-based energy storage composite dielectric film with excellent high-temperature energy storage properties, characterized in that: The method: S1: dissolving polyetherimide in N-methylpyrrolidone, then adding a core-shell structure filler, mixing, and removing bubbles to obtain a slurry; the preparation method of the core-shell structure filler is: using boron nitride as a target material and magnesium oxide particles as a substrate, bombarding the target material with magnetron sputtering to coat a boron nitride shell layer on the surface of the magnesium oxide particles, the magnetron sputtering process: power 50-70W, time 1.5-3h, target-substrate distance 15-18cm, magnesium oxide particle size 250-300nm, shell thickness 40-100nm; the mass ratio of the core-shell structure filler to the polyetherimide is (0.01-0.02): 1; S2: The obtained slurry is made into a wet film by doctor blade coating, and then dried by gradient heating to obtain a polyetherimide-based energy storage composite dielectric film.

2. The method according to claim 1, characterized in that: The slurry concentration in S1 is 0.1-0.15 g / mL, and S1 is defoamed by vacuuming. The gradient temperature rising program in S2 is: 60-80°C for 3-5 h, 110-130°C for 1-3 h, 140-160°C for 1-3 h, 180-220°C for 1-3 h, and finally kept at 180-220°C under vacuum for 3-5 h.

3. Application of the polyetherimide-based energy storage composite dielectric film having excellent high-temperature energy storage characteristics obtained by the method of claim 1 or 2 in capacitors.